Voltage distribution in inorganic insulation windings for high-temperature motors. Issue 6 (7th November 2016) - Roger, Daniel; Iosf, Vadim; Babicz, Sylvain
Abstract : Purpose: The purpose of this paper is to present a method for computing voltage spikes endured by the insulation of the first coils of high-temperature (HT°) synchronous machines fed by PWM inverters that deliver fast-fronted voltage pulses. Design/methodology/approach: The transient state following each steep edge is computed by SPICE using the global high-frequency (HF) equivalent circuit of the motor winding. This equivalent circuit is automatically built using the proposed elementary coil model. Two inorganic HT° technologies are compared: the first one uses a round copper wire insulated by a thin ceramic layer and the second one is made with an anodized aluminum strip. Findings: The winding made with an anodized aluminum strip, which has a higher turn-to-turn capacitance, yields a better voltage distribution between coils of the machine. Research limitations/implications: The elementary coil equivalent circuit is computed from impedance measurements performed on an elementary coil. Another starting point could be developed with an FE analysis to determine the parameters of the HF equivalent circuit, which would avoid the need for a prototype coil before the machine design. Practical implications: For inorganic motors, the insulation layers have poorer electrical characteristics compared with standard organic ones. Therefore, the computation of voltage spikes distribution along the coils of each phase represents a major issue in the design of HT° machines. Originality/value: The presented approach is a step toward the design of HT° (400-500°C) actuators fed by PWM inverters based on fast SiC electronic switches.